The effect of soil cultivation systems on agronomic and physical properties of dark gray soil and productivity of the field crop rotation link - D. A. Dementyev; A. A. Fadeev (Аграрная наука Евро-Северо-Востока)
The purpose of the research is to identify the most effective and preferable variant of the basic autumn tillage for inclusion of dark gray forest soil into the tillage system when sowing spring crops. The research was carried out in 2021–2023 in the conditions of the Chuvash Republic in the link of the field crop rotation "barley–peas–oats". Moldboard and non-moldboard autumn soil tillage methods were compared: plowing (26–28 cm) – control; cultivation (15–17 cm); disking (12–14 cm); without tillage. The tillage system was completed by surface early pre-sowing cultivation to a depth of 6 cm. During the studied years, the average soil density in the 0–30 cm layer was within the optimal values: after moldboard plowing it was 0.93–1.09 g/cm3 , after cultivation – 0.98–1.13 g/cm3 , without basic tillage– 1.05–1.20 g/cm3 . The average values of the soil porosity after plowing were in the range of 50.4–62.5 % and decreased with the abandonment of the basic tillage to 52.0–57.4 %. In arid conditions of 2021 growing season, the total supply of productive moisture in the 0–30 cm soil layer was 12–14 % higher after cultivation than after plowing. The analysis of the structural and aggregate state of the soil (0–20 cm) revealed an increase in the proportion of dusty particles by the end of the experiment after plowing from 3.9 to 6.9 %. When using a stubble cultivator as the basic tillage unit, the proportion of the lumpy fraction increased. The average annual productivity of the crop rotation link during moldboard plowing was the highest – 20.5 c/ha of grain units per 1 ha, after cultivation – 19.5 c of grain units per 1 ha. At the same time, plowing is the most expensive and economically unprofitable way of basic soil preparation. After cultivation with a KOS-3.0 combined stubble cultivator, the profitability of crop cultivation was significantly higher – 9.4–18.1 % after cereals in dry years and 96.9 % after peas under optimal hydrothermal conditions (for plowing – 8.3–4.2 % and 73.7 %, respectively).